Asymptotic Expansions for Large Degree Tangent and Apostol-Tangent Polynomials of Complex Order - Cristina B. Corcino; Roberto B. Corcino; Jeremar Casquejo (Journal of Applied Mathematics, 2023)
This paper provides asymptotic expansions for large values of n of tangent Tnμz and Apostol-tangent Tnμz;λ polynomials of complex order. The derivation is done using contour integration with the contour avoiding branch cuts.